Risk stratification of gastric cancer screening in community population based on oral contrast-enhanced ultrasonography examination: A 3-year follow-up analysis report - Guan, Sainan; Yan, Ronghua; Chen, Xiaomin; Chen, Weiqiang; Zhou, Xi; Zhou, Minghui; Xie, Zhengneng; Tan, Wen; He, Yongyan; Fu, Juan; Yuan, Fan; Xu, Erjiao (Frontiers in Oncology, 2023)
Objective: This study aimed to retrospectively investigate the use of oral contrast-enhanced ultrasonography (O-CEUS) in assessing the thickness of the gastric wall for gastric cancer (GC) screening and to establish screening strategies for GC with different risk stratifications based on the gastric wall thickness.Methods: From January 2015 to March 2020, people who underwent O-CEUS at the Physical Examination Center of our hospital with at least three years of follow-up were included in this study.The thickness of the gastric wall measured by O-CEUS was divided into three groups using 6 mm and 9 mm as cutoff values. The occurrence of GC in each group was observed. The imaging and clinical information of these populations were recorded and analyzed. Kaplan-Meier survival analysis and Cox's proportional hazards regression were performed to calculate the risk of GC occurrence.Results: A total of 4,047 people were finally included in this study. During the follow-up period, GC occurred in 7 individuals (incidence rate 0.17%). Among them, according to the thickness of the gastric wall, one case occurred in Group A (< 6 mm), two cases occurred in Group B (6-9 mm), and four cases occurred in Group C (＞9mm). Based on Kaplan-Meier survival analysis, the curves of the three groups were significantly different (P < 0.01). The risk of GC occurrence in Group C and Group B were higher than that in Group A (4.76E+2-fold and 1.50E+2-fold).Conclusion: O-CEUS is a convenient, economical, safe, and noninvasive screening method for GC.Measuring the thickness of the gastric wall is helpful to predict the risk of GC occurrence according to our stratification screening system.